PSYCHOLOGICAL FUNDAMENTALS OF FOREIGN LANGUAGE TEACHING - Ravshanova, Tursunoy (Журнал иностранных языков и лингвистики, 2020)
This article provides information on the psychological basis of foreign language teaching. High results can be achieved if teachers organize the teaching process correctly, taking into account that the teaching of foreign languages at school is a period when the school-age student has a high level of intelligence, sensitivity, observation, reading and memory skills. illuminated.